SENSITIVITY AND SPECIFICITY OF BACTERIAL CULTURE USING VITEK-2 FROM SPUTUM FOR DETECTING KLEBSIELLA PNEUMONIA AND ACINETOBACTER BAUMANII BACTERIA IN PNEUMONIA PATIENTS AT HAJI ADAM MALIK GENERAL HOSPITAL MEDAN - Andrie Wiguna, Franciscus Ginting & Armon Rahimi (International Journal of Research Science and Management, 2020)
Introduction: Nosocomial infections are a cause of worldwide morbidity and mortality, a problem is getting worsen when nosocomial pathogens get antibiotic resistance. In Asian countries, antimicrobial resistance to common pathogens of Hospital-Acquired Pneumonia (HAP). Based on Microbiological culture data reports at H. Adam Malik General Hospital in 2017 within 2622 sputum isolates, the most common was Klebsiella pneumonia (16.55%) and Acinetobacter baumanii (17.6%). Detection of bacteria that produce extended-spectrum betalactamase (ESBL) is very important for infection control and epidemiological surveillance. The method used is VITEK-2 and PCR (Polymerase Chain Reaction). Aim: To evaluate the sensitivity and specificity values in the diagnostic test of bacterial sputum culture examination with VITEK-2 and PCR in detecting K. pneumonia and A.baumanii bacterias. Methods: The diagnostic test uses primary data based on the results of sputum culture and secondary data based on medical records in pneumonia patients who are hospitalized in H. Adam Malik General Hospital Medan. The sampling technique uses consecutive sampling method on 50 respondents. Data were analyzed using SPSS version 20. Result: The diagnostic test results using the VITEK-2 test in detecting both K. pneumonia and A. baumanii showed sensitivity (93%) and specificity (100%). The evaluation of sensitivity and specificity in detecting K. pneumonia was (93.3%) and (100%) higher than in detecting A.baumanii was (76.4%) and (100%). Conclusion: VITEK-2 method can be used in diagnosis and screening in detecting bacteria K. pneumonia and A.baumanii in pneumonia. The sensitivity value of this method is higher in detection of K. pneumonia than A.baumanii